STUDI KASUS PRODUCT LIFE CYCLE WASHINGTON MUTUAL - Trisna, Amadea Ayu; Adwidya, Clementine Widyadhari Btari; Wicaksono, Soetam Rizky (LPPM Universitas Malikussaleh, 2025)
This study examines the failure of Washington Mutual (WaMu), one of the largest financial institutions in the United States, to maintain the product life cycle (PLC) of its products. Founded in 1889, Washington Mutual grew rapidly through aggressive expansion and a focus on the mortgage market. However, this strategy led to the accumulation of significant risks, primarily through exposure to subprime mortgages. The inability to manage these risks, combined with a lack of innovation in product development and adaptation to market changes, caused WaMu to lose its competitiveness. In addition, a less flexible business model and lack of service diversification reduced the relevance of WaMu's products in an increasingly competitive market. This study identified internal factors such as poor risk management, low operational efficiency, and failure to innovate, as well as external factors such as changing consumer preferences and pressure from competitors, as the main causes of WaMu's failure to maintain the sustainability of its products. In conclusion, Washington Mutual's failure to maintain the PLC cycle reflects the importance of strategic adaptation and continuous innovation in dealing with the dynamics of the banking industry.